2016
DOI: 10.1016/j.pscychresns.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation potentiates glutamatergic neurotransmission in depressed adolescents

Abstract: Abnormalities in glutamate neurotransmission may have a role in the pathophysiology of adolescent depression. The present pilot study examined changes in cortical glutamine/glutamate ratios in depressed adolescents receiving high-frequency repetitive transcranial magnetic stimulation. Ten adolescents with treatment-refractory major depressive disorder received up to 30 sessions of 10-Hz repetitive transcranial magnetic stimulation at 120% motor threshold with 3,000 pulses per session applied to the left dorsol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 45 publications
3
82
0
Order By: Relevance
“…Levkovitz et al (2009) studied different deep TMS settings in 65 adults with MDD and found that high intensity (120% of MT) but not low-intensity (110% of MT) deep TMS for 4 weeks was an effective treatment (and no participants in the study experienced seizures) (Levkovitz et al 2009). Although one of the initial pilot studies in adolescents with depression (using a standard, figure-8 coil) used lower intensity (Mayer et al 2012), the other work has used 120% intensity with no reported seizures to date (Wall et al 2011;Croarkin et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Levkovitz et al (2009) studied different deep TMS settings in 65 adults with MDD and found that high intensity (120% of MT) but not low-intensity (110% of MT) deep TMS for 4 weeks was an effective treatment (and no participants in the study experienced seizures) (Levkovitz et al 2009). Although one of the initial pilot studies in adolescents with depression (using a standard, figure-8 coil) used lower intensity (Mayer et al 2012), the other work has used 120% intensity with no reported seizures to date (Wall et al 2011;Croarkin et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used 1 H-MRS in this context (Croarkin et al, 2016; Dubin et al, 2016; Godlewska et al, 2015; Grimm et al, 2012; Jarnum et al, 2011; Luborzewski et al, 2007; Merkl et al, 2011; Michael et al, 2003; Njau et al, 2016; Pfleiderer et al, 2003; Taylor et al, 2012; Yang et al, 2014; Zhang et al, 2013), but are characterized by important methodological limitations. First, many of these studies measured Glx – a composite measure containing both glutamate and glutamine – making them difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…Participants underwent structural MRI and TE-optimized proton MRS using a method similar to that published previously (Croarkin et al, 2016). Briefly, scans were obtained using a General Electric 3 T Discovery MRI scanner (GE Medical Systems, Inc., Waukesha, WI, USA) equipped with an 8-channel head coil.…”
Section: Methodsmentioning
confidence: 99%
“…This region encompassed the hand knob of the precentral gyrus (Brodmann area 4) that was presumably interrogated with TMS. The ACC voxel was positioned as previously described (Croarkin et al, 2016), encompassing the pregenual ACC of both hemispheres (Brodmann areas 24a, 24b and 32). A TE-optimized PRESS sequence (PROBE-P, TR = 2000 ms, TE = 80 ms, 128 acquisitions, 5000 Hz bandwidth, 2048 points) was used to obtain spectroscopic data for both voxel locations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation